Antithrombotic Effect of a Recombinant von Willebrand Factor, VCL, on Nitrogen Laser-Induced Thrombus Formation in Guinea Pig Mesenteric Arteries - Azzam, K; Garfinkel, L I; dit Sollier, C Bal; Thiam, M Cisse; Drouet, L (Thrombosis and Haemostasis, 1995)
To assess the antithrombotic effectiveness of blocking the platelet glycoprotein (GP) Ib/IX receptor for von Willebrand factor (vWF), the antiaggregating and antithrombotic effects were studied in guinea pigs using a recombinant fragment of vWF, Leu 504-Lys 728 with a single intrachain disulfide bond linking residues Cys 509-Cys 695. The inhibitory effect of this peptide, named VCL, was tested in vitro on ristocetin- and botrocetin-induced platelet aggregation and compared to the ADP-induced platelet aggregation. In vivo, the antithrombotic effect of VCL was tested in a model of laser-injured mesentery small arteries and correlated to the ex vivo ristocetin-induced platelet aggregation. In this model of laser-induced thrombus formation, five mesenteric arteries were studied in each animal, and the number of recurrent thrombi during 15 min, the time to visualization and time to formation of first thrombus were recorded.In vitro, VCL totally abolished ristocetin- and botrocetin-induced platelet aggregation, but had no effect on ADP-induced platelet aggregation. Ex vivo, VCL (0.5 to 2 mg/kg) administered as a bolus i. v. injection inhibits ristocetin-induced platelet aggregation with a duration of action exceeding 1 h. The maximum inhibition was observed 5 min after injection of VCL and was dose related. The same doses of VCL had no significant effect on platelet count and bleeding time. In vivo, VCL (0.5 to 2 mg/kg) had no effect on the appearance of the thrombi formed but produced dose-dependent inhibition of the mean number of recurrent thrombi (the maximal effect was obtained at 5 min following i. v. injection of the highest dose: 0.8 ± 0.2 thrombi versus 4 ± 0.4 thrombi in controls). The three doses of VCL increased the time in which the first thrombus in a concentration-dependent manner was formed. However, the time to visualize the first thrombus was only prolonged in the higher dose-treated group.These in-vivo studies confirm that VCL induces immediate, potent, and transient antithrombotic effects. Most importantly, this inhibition was achieved without inducing thrombocytopenia nor prolongation of the bleeding time.